Policymakers' Perceptions of the Use of Deliberative Mini-Publics to Support Sustainability Policies - Saarikoski, Heli; Ojanen, Maria; Hilden, Mikael; Mela, Hanna; Huttunen, Suvi; Kulha, Katariina; Soini, Katriina; Sorvali, Jaana (John Wiley & Sons, 2026)
Deliberative mini-publics (DMPs) have emerged as a novel method to deepen public participation in complex and contentious policy decisions, such as those related to sustainability transformations. Despite an increasing interest in applying DMPs in environmental governance, little is known about policymakers' expectations regarding their applicability and impact. We address this research gap by exploring policymakers' perceptions of DMPs in a sustainability policy context, drawing on a qualitative analysis of focus group and interview data with Finnish policymakers. The results show that policymakers welcome DMPs as a promising addition to the repertoire of public engagement methods but only in an occasional and consultative role, without a formal place in decision-making. They felt that DMPs can promote active citizenship and reasoned debate, especially if they are combined with other participatory processes such as public hearings as well as wider communication processes that contribute to the deliberative capacity of the ‘maxi-public’. At the same time, they were concerned over the representativeness of DMPs as well as citizens' capacities to grasp complex sustainability problems in a short time frame. A systematic collection of experiences from DMPs and regular reflection on their utility with policymakers would strengthen the role of DMPs in developing policies for sustainability transitions.